[Effect on quality of life of nCPAP treatment in patients with obstructive sleep apnea]. - Mar, J; Rivero-Arias, O; Durán-Cantolla, J; Alonso-Alvarez, M; Gaminde, I; de la Torre-Muñecas, G (2005)
BACKGROUND AND OBJECTIVE: The standard treatment of the obstructive sleep apnea syndrome (OSAS) is the nCPAP. There is evidence that its use improves the quality of life of patients. The objective of the study is to measure the effect of nCPAP on the quality of life of patients in a Spanish cohort. PATIENTS AND METHOD: We have used 3 quality of life questionnaires: SF-36, EuroQol 5D and FOSQ. OSAS patients were interviewed at baseline prior to the start of the treatment and at 3 months follow-up. Two measures were employed to analyze the data: distribution based measures such as the effect size and instruments that evaluate the sensitivity to change of the questionnaires such as the ROC curves. RESULTS: We interviewed 124 patients. The benefit in terms of utility of the nCPAP was 0.03 with SF-36 and 0.04 with EuroQol 5D. Effect size varies from small (0.21) with EuroQol 5D to moderate (0.51) with FOSQ. SF-36 obtained intermediate scores (0.35). EuroQol 5D was the questionnaire that obtained the biggest area under the ROC curve. Nevertheless, the area size was small in all cases. CONCLUSIONS: nCPAP improves significantly the quality of life of OSAS patients. The assessment of the quality of life of OSAS patients with the available instruments is only partially satisfactory.